PENGARUH PENGUNGKAPAN GREEN BANKING DAN ISLAMIC SOCIAL REPORTING TERHADAP NILAI PERUSAHAAN BANK SYARIAH - Khoer, Misbahul; Nur Hidayatullah, Atep; Algistiana, Algistiana (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
This study examines the influence of Green Banking and Islamic Social Reporting (ISR) Disclosure on Firm Value in Islamic Banks listed on the Indonesia Stock Exchange (IDX). The urgency of this research arises from regulatory obligations (POJK 51/2017) regarding sustainable finance, as well as the inconsistency in the quality of Green Banking and ISR disclosures among Islamic banks, which have the potential to influence investor perceptions and Firm Value in the capital market. This study uses a quantitative approach with a descriptive survey method. Data analysis techniques applied include classical assumption tests, correlation coefficients, determination coefficients, t-tests, multiple linear regressions, and F-tests. The research population is all Islamic Banks listed on the IDX, with samples selected using purposive sampling techniques. The results of the study indicate that: (1) Green Banking Disclosure has a positive and significant effect on Firm Value. (2) Islamic Social Reporting Disclosure also has a positive and significant effect on Firm Value, even with a more dominant contribution. (3) Green Banking and Islamic Social Reporting Disclosure simultaneously (together) have a significant effect on Firm Value. The implications of this research emphasize that the integration of environmental commitment (Green Banking) and Islamic Social Reporting (ISR) is a crucial factor for Islamic Banks to build market trust and optimize Company Value.